2016
DOI: 10.12998/wjcc.v4.i8.202
|View full text |Cite
|
Sign up to set email alerts
|

Lateral patellofemoral ligament reconstruction to restore functional capacity in patients previously undergoing lateral retinacular release

Abstract: This novel technique for LPFL reconstruction is effective at restoring lateral restraint of the patellofemoral joint and improving joint functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Beckert et al. 9 described yet another technique using a hamstring allograft with suspensory femoral fixation and sutured patellar fixation in 19 knees, showing no postoperative apprehension and improved Knee Injury and Osteoarthritis Outcome Score. Although these early results are promising, further research is needed to determine optimal techniques and evaluate long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beckert et al. 9 described yet another technique using a hamstring allograft with suspensory femoral fixation and sutured patellar fixation in 19 knees, showing no postoperative apprehension and improved Knee Injury and Osteoarthritis Outcome Score. Although these early results are promising, further research is needed to determine optimal techniques and evaluate long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchis-Alfonso et al 8 reported on 17 knees at 18 to 48 months postoperatively using ITB autograft and found similarly improved Lysholm scores and improved psychometrics postoperatively. Beckert et al 9 described yet another technique using a hamstring allograft with suspensory femoral fixation and sutured patellar fixation in 19 knees, showing no postoperative apprehension and improved Knee Injury and Osteoarthritis Outcome Score. Although these early results are promising, further research is needed to determine optimal techniques and evaluate long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The graft is fixed at the femur with suspensory fixation, and the 2 limbs are sutured to the anterior aspect of the patella. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Several methods of LPFL reconstruction have been described, with primary differences consisting of graft choice and patellar fixation. 5 , 6 , 7 , 8 , 9 …”
mentioning
confidence: 99%